Perancangan dan Implementasi Sistem Pengendalian Manajemen Berbasis Microsoft Access pada Pengelolaan Keuangan PT. Vibe Akademik Bahasa - Iskandar Itan; Hennie Selviani (BADAN PENERBIT STIEPARI PRESS, 2025)
Financial data management at PT. Vibe Akademik Bahasa was previously done manually using Microsoft Excel, which resulted in inefficiency and delays in calculations and reporting. To overcome this problem, this activity designed a management control system using Microsoft Access that automates student data recording, payment transactions, and the issuance of invoices and financial reports. This activity used observation, interviews, and document analysis to identify user needs, followed by system design that included the design of data input forms and payment transactions. The resulting system enables automatic invoice issuance based on student identification numbers, supports payment recording, and provides real-time profit and loss reports that can be accessed by partner institutions. This implementation demonstrates that a database-based management control system can improve accuracy, timeliness, and transparency in financial data management. Further activities are recommended to enhance the system with web-based access, multi-user functionality, and integration with other financial tools to improve operational efficiency and scalability.